Pengaruh Penerapan Video Pembelajaran Melalui Google Classroom Pada Materi Larutan Elektrolit dan Non Elektrolit Terhadap Hasil Belajar Siswa di SMA N 1 Langowan - Merly Mira Mangirang; Soenandar Milian Tompunu Tengker (Oxygenius Journal Of Chemistry Education, 2022)
The purpose of this study was to determine the effect of the application of learning videos through Google Classroom on the learning outcomes of X Mipa 4 students at SMA N 1 Langowan. This research is a quantitative research using experimental method using One-Group pretest-posttest design. The population taken is all class X MIPA SMA N 1 Langowan, the sample consists of 1 class, namely X MIPA 4 as an experimental class, totaling 32 students. Data collection was done by giving a pretest before the learning process was carried out, and a posttest after the learning process. Data The results obtained in the form of the difference between the pretest and posttest in the experimental class are 40.4 and the average pretest is 47.7, while the posttest average is 88.1. get that the data is normally distributed. Furthermore, the test through t-test, the results obtained between the experimental class are significant, namely tcount = 18.60 > ttable = 1.998. Thus, it can be concluded that the Google Classroom learning media which contains video can affect student learning outcomes.